MERDEKA BELAJAR DALAM PEMBELAJARAN AGAMA HINDU PERSPEKTIF FILSAFAT PENDIDIKAN PROGRESIVISME - Gede Agus Siswadi (Jurnal Pendidikan Agama, 2023)
Freedom to learn is a new education policy in Indonesia that requires a big change for the better than the previous education. Freedom to learn is present as an instrument that was born from the merger of educational theory and previous policies. Freedom to learn and the educational philosophy of progressivism have the same goal, namely to provide a wide space for students, teachers, and also educational institutions to design a series of learning that is liberating, democratic, independent, and also free to innovate. This study uses a qualitative method with a philosophical hermeneutic approach and uses Miles and Huberman's data analysis patterns. The results of this study are the educational philosophy of progressivism emphasizes that students must develop naturally, experience is the key word in motivating children's learning, teachers act as facilitators in learning, and the curriculum must be designed student-centred. The concept of independent learning in principle provides a wide space for exploring the greatest potential for teachers and students to innovate and improve the quality of learning independently. Then the application of freedom to learn in Hindu religious learning is to provide space for students, teachers, and schools to always are free in thinking, free to innovate, and independent in creativity so that the concept of education that relies on "sa vidya ya vimuktaye" or learning is what liberating humanity can be achieved.